Methods of independent reading and their influence on student knowledge about human anatomy, physiology, and hygiene - Griniuvienė, O. (Psichologija, 1966)
While science is developing rapidly, the programs and textbooks fall inevitably behind it. The school has a new challenge – not only to teach students, but to educate them to keep learning. Educating the students to read systemically the popular science literature is becoming more important.The article describes the experiment which is aimed to determine the influence of various reading methods on the student knowledge, and to find the proper methods in organizing the extracurricular readings on the courses of human anatomy, physiology and hygiene. The data of experimental classes were compared to the data from four different schools where the extracurricular reading was not practiced.Conclusions:1) home tasks that require extracurricular reading can be an effective method in encouraging the students to read;2) extracurricular reading deepens the knowledge and helps in memorizing it;3) the vivid description from a teacher is only needed when the book is not available for the students, but it cannot replace the independent reading.
Keywords: home reading; human anatomy; human physiology; human hygiene; extracurricular reading